Severe Persistent Contagious Ecthyma Cases in Twin Goats - Issi, M.; Gulacti, I.; Bulut, H.; Gul, Y. (Medwell Online, 2010)
In the present study, severe persistent orf cases affecting only twin kids following an oil outbreak in a flock is reported to contribute the discussions on severe persistent form of orf Although, oil lesions occurred only around the mouth of most of kids of the flock of 230 hair goats, 12 twin kids had lesions around mouth, feet, eye lids and anus area A 2 month old kid suspected of orf was admitted to the clinics of Faculty of Veterinary Medicine University of Firat, Turkey The kid was clinically examined and samples were collected for hematological and virological examinations The results confimed the presence of severe persistent form of orf In conclusion, the results may contribute to the discussions going on over the pathogenesis of the severe persistent form the disease
Keywords: Goat; contagious ecthyma; severe persistent orf; polymerase chain reaction; pathogenesis; virological examinations